2018
DOI: 10.3390/su10124743
|View full text |Cite
|
Sign up to set email alerts
|

Mapping ICT Use along the Citrus (Kinnow) Value Chain in Sargodha District, Pakistan

Abstract: The value chains of fresh fruits and vegetables are sensitive to timeliness and require a quick information flow. Keeping in view its importance, this study has focused on mapping the use of information and communication technologies (ICTs) along the citrus value chain, including information channels being used, factors influencing ICT use, challenges, and weaknesses faced by value chain stakeholders. Cross-sectional data were mainly collected by structured and semi-structured interviews with value chain stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This meaning that, smallholder farmers who lived in the remote areas far from the extension office were more likely to sell to closer markets as the indirect marketing channels and reduced their profits. This result was consistent with Waqar et al (2018) found that negatively significant distance from farm to the extension office.…”
Section: Influencing Factors In the Wet Seasonsupporting
confidence: 92%
See 1 more Smart Citation
“…This meaning that, smallholder farmers who lived in the remote areas far from the extension office were more likely to sell to closer markets as the indirect marketing channels and reduced their profits. This result was consistent with Waqar et al (2018) found that negatively significant distance from farm to the extension office.…”
Section: Influencing Factors In the Wet Seasonsupporting
confidence: 92%
“…According to Waqar et al (2018) revealed that negatively significant distance from farm to the extension office. Therefore, DEO of the variable was expected to decrease the likelihood of using direct marketing channels in the wet and dry season.…”
Section: Description Of Independent Variablesmentioning
confidence: 99%
“…Citrus is an important cashfruit crop of Pakistan grown on a large scale about 170, 000 ha of land in Pakistan, comprising about 30 % of the area under all fruit orchards [3]. It is the 4 th most important commodity of Pakistan after rice, alcohol and wheat [4]. The major citrus variety grown in Punjab is "Kinnow mandarin," a cross between King (C. nobilis Lour) and willow mandarin (C. deliciosa Tenoras).…”
Section: Introductionmentioning
confidence: 99%